Using Social Media as Self-Disclosure Media (Multimodal Discourse Analysis of Gay Homosexual Content on TikTok) - Akhmad Salafuddin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Use of Social Media as a Self-Disclosure Media (Multimodal Discourse Analysis of Gay Homosexual Content on TikTok Social Media). The purpose of this study was to determine the use of social media TikTok as a medium for self-disclosure carried out by gay homosexuals in Indonesia. This is a new phenomenon where previously gay homosexuals choose to hide themselves because they experience discrimination and are considered abnormal by some people, but now several gay homosexuals have started to reveal themselves even through social media which has an unlimited range of users. This study uses a qualitative approach, with data collection techniques from gay homosexual content uploaded on TikTok, observations with TikTok who give reactions in the form of likes, comments, re-shares, to do a duet or stitch on gay homosexual content, as well as in-depth interviews with gay homosexuals. The method used in this research is Guther Kress & Theo Van Leeuwen Multimodal Discourse Analysis. This analysis refers to the way people communicate using several fashion semiotics in product design such as visuals, audiovisuals, text, and interactivity on likes, comments, re-shares, to duets or stitches social media TikTok. The analysis in this study refers to 3 (three) analysis systems, namely information value, salience, and framing.